Isotope Analysis of 18O and 2H: A Coastal Confined Aquifer Case Study - Nugraheni, Vania Salsabila Anabel; Santi, Narulita; Putranto, Thomas Triadi; Marin, Jenian; Hidayatillah, Ahmad Syauqi (Universitas Diponegoro, 2025)
In 2023, groundwater quality in Semarang declined due to excessive extraction, leading to land subsidence and reduced groundwater availability. Prolonged dry seasons caused drought in ten villages across five sub-districts. This study aims to investigate geological conditions, groundwater flow patterns, and the spatial distribution of pH, TDS, hardness, electrical conductivity, and major ions (Na⁺, Ca²⁺, Cl⁻, and HCO₃⁻). Additionally, it seeks to interpret groundwater evolution through Gibbs diagram analysis and identify groundwater origins using stable isotopes (¹⁸O and ²H). The methodology involves stable isotope analysis to trace groundwater sources and evaluate d-excess values, which are linked to drought conditions and recharge mechanisms. Water chemistry analysis was performed to characterize ion concentrations, while the Gibbs diagram was used to identify the dominant geochemical processes influencing groundwater. The study area comprises claystone, marl, sandstone, volcanic breccia, and alluvium, with 60 sampling points spanning Upper and Lower Semarang. Water types identified include NaHCO₃, NaCl, CaHCO₃, MgHCO₃, and NaSO₄. NaHCO₃ was the most common, followed by NaCl and CaHCO₃. Isotope analysis revealed several points with d-excess <10 (e.g., SB-10L, SB-20L, SA-4, SA-8, SA-29), indicating groundwater recharge from modern rainfall, typically characterized by d-excess values >10.